PENGUJIAN KUAT TEKAN BETON MENGGUNAKAN BAHAN TAMBAH PLASTIK JENIS POLYETHYLEN TEREPHTALATE - Toya, Ikran (Universitas Tadulako, 2025)
Abstract The use of plastic additives in various items such as household appliances and electronics is common in society. One type of plastic, Polyethylene, is produced through the polymerization process of ethylene gas. However, plastic is difficult to decompose naturally, requiring hundreds of years to decompose completely. Therefore, the utilization of plastic waste into building materials such as concrete is an innovative alternative, especially PET (Polyethylene Terephthalate) plastic from recycled beverage bottles. This study aims to determine the compressive strength of concrete with coarse aggregate added from PET plastic waste. In Banggai Regency, the use of plastic waste in concrete has not been carried out or tested with local materials. This study was conducted experimentally in the Banggai Regency laboratory with PET variations of 0%, 3%, 6%, and 9%. The highest results were obtained in a mixture of 3% PET with a water cement ratio (FAS) of 0.5, namely 25 MPa. Meanwhile, FAS 0.6 produced the highest compressive strength in the 0% PET variation, namely 19.9 MPa. The difference in results in the 3% PET variation between FAS 0.5 and 0.6 reached 26%. This shows that the FAS composition and PET content have a significant effect on the compressive strength of concrete.. Keywords: concrete, concrete compressive strength, PET plastic, additional materials